Pelatihan Pembelajaran Deep Learning Berbasis STEAM untuk Guru Sekolah Dasar - Zainil, Melva; Netrawati, Netrawati; Arwin, Arwin; Kenedi, Ary Kiswanto; Suherman, Dea Stivani; Mardin, Asna (Universitas Pahlawan Tuanku Tambusai, 2025)
This training on the development and implementation of STEAM-based deep learning was designed to enhance the capacity of elementary school teachers in preparing for the interdisciplinary-focused National Curriculum. The program was motivated by teachers’ limited understanding of deep learning and their difficulty in integrating STEAM elements into lesson planning. The methods included training, lesson plan workshops, teaching simulations, technology diffusion, and classroom mentoring. Results showed a significant increase in conceptual understanding, technical skills, and teacher creativity in designing and implementing project-based and collaborative learning. The resulting integrative lesson plans and creative teaching media served as indicators of the program’s success. These outcomes highlight the importance of localized teacher professional development programs to accelerate readiness for implementing STEAM-oriented curricula in primary education settings.